Hydroxymethylglutaryl-CoA reductase inhibitors (statins) for the treatment of sepsis in adults – A systematic review and meta-analysis. (March 2019) - Pertzov, B.; Eliakim-Raz, N.; Atamna, H.; Trestioreanu, A.Z.; Yahav, D.; Leibovici, L.
Abstract: Objectives: The pleiotropic effect of hydroxymethylglutaryl-CoA reductase inhibitors (statins) might have a beneficial effect in sepsis through several mechanisms. The aim was to assess the efficacy and safety of statins, compared with placebo, for the treatment of sepsis in adults. Methods: We searched the following databases: the Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library, 2017, Issue 12), OVID MEDLINE (from 1966 to January 2018), Embase (Ovid SP, from 1974 to January 2018), and LILACS (from 1986 to January 2018). We also searched the trial registries ISRCTN andClinicalTrials.gov to January 2018. The eligibility criteria were randomized controlled trials comparing the treatment of statins versus placebo in adult patients who were hospitalized due to sepsis. Participants were adults (16 years and older) hospitalized because of sepsis or who developed sepsis during admission. Interventions were treatment with hydroxymethylglutaryl-CoA reductase inhibitors (statins) versus no treatment or placebo. We performed a systematic review of all randomized controlled trials published until January 2018, assessing the efficacy and safety of statins in sepsis treatment. Two primary outcomes were assessed: 30-day overall mortality and deterioration to severe sepsis during management. Secondary outcomes were hospital mortality, need for mechanical ventilation and drug related adverse events. Results: Fourteen trials evaluating 2628 patients were included. Statins did not reduce 30-day all-cause mortality neither in all patients (risk ratio (RR) 0.96, 95% confidence interval (CI) 0.83–1.10), nor in a subgroup of patients with severe sepsis (RR 0.97, 95% CI 0.84–1.12). The certainty of evidence for both outcomes was high. There was no change in the rate of adverse events between study arms (RR 1.24, 95% CI 0.94 to 1.63). The certainty of evidence for this outcome was high. Conclusions: The use of statin therapy in adults for the indication of sepsis is not recommended.